Stay alive [videorecording] safety for journalists (Philippine Center for Investigative Journalism, 2006)
Philippines has been called one of the most dangerous places in the world for journalists. Fifty-six have been killed in the last two decades, and many other threatened for exposing wrongdoing committed by people in power. A video of practical tips that journalists can apply in dealing with threats to their lives and safety. Its message is that journalists need not and should not be sitting targets they can and be should take steps to protect themselves and deter would-be assassins.